PHP and MySQL web development - Welling, Luke (Developer's library., 2009)
Aims to teach you to develop dynamic, secure, commerical Web sites. This fourth edition reflects the changing landscape of MySQL and PHP. It incorporates changes in the 5.1 specs of PHP and MySQL. It also covers topics such as Ajax, social networking sites, security concerns, and the PEAR repository of PHP extensions and applications.